EFFECT OF CLOSURE VERSUS NON-CLOSURE OF PARIETAL PERITONEUM AT CAESAREAN SECTION ON ADHESION FORMATION. - Rahem, Gona Aziz (Journal of Sulaimani Medical College, 2021)
Background Caesarean section (CS) is a standard obstetric procedure, and it is rate increasing worldwide. However, intraabdominal adhesion is one complication of caesarean section and other obstetric and gynaecological surgeries. Objectives This study aims to compare the frequency and severity of post-surgical adhesions among patients with closed and non-closed parietal peritoneum at their first caesarean section. Patients and Methods A cross-sectional study was conducted in maternity and private hospitals in Sulaymaniyah/Kurdistan/Iraq, from July 2015 to December 2020. Involved 190 pregnant ladies entered second CS at term. Patient records were then abstracted to assess prior CS techniques, including parietal peritoneal closure, which the same obstetrician did. A total of 190 patients were checked for that purpose; each was checked to know whether she has intra-abdominal adhesion or not and at the same time to know whether her previous CS was performed by peritoneal closure or not. The main parameters were adhesion formation in the second CS and the type of adhesion. The maternal age, occupation, parity, and gestational age were also recorded—Chi-square test used for statistical analysis of variables. Results Based on the outcome, two groups (one with peritoneal closure and the other without it) were identified, they were compared regarding their maternal age, parity, gestational age and occupation. There was significantly more adhesion between the omentum and Scarpa fascia in the non-closure group (28.3%) compared to (13.1%) in the closure group with (p-value 0.01), which is significant. On the other hand, filmy adhesion was more in the closure group (63.6%), while thick adhesion was more in the non-closure group (53.3%) with (p-value 0.34), which is not significant. Conclusion Parietal peritoneum closure at first caesarean section was associated with less adhesion formation. Therefore, the practice of non-closure of parietal peritoneum at caesarean delivery is not recommended.
Keywords: Caesarean section; Peritoneum; Closure; Non-closure; Adhesion